A quasi-experimental study on a co-production- and school-based psychosocial well-being program in Hong Kong - Angel Hor Yan Lai; Shijuan Wei; Kylie Wing Yin Wong; Xuning Zhong; Jiacheng Sun (Scientific Reports)
Abstract This study investigated the effects of “Healing Space,” a co-production- and school-based initiative aimed at promoting positive psychosocial health among secondary school students in Hong Kong. Designed according to the Self-Determination Theory, Healing Space sought to enhance positive mental health attitudes, psychological well-being, and social connectedness among participants. Using a two-wave quasi-experimental design, students completed baseline and post-test assessments using standardized measurements based on their program participation (service co-producer group: n = 171; service user group: n = 400; waitlisted control group: n = 348). The results demonstrated significant interaction effects between ‘time’ and ‘group’ on self-compassion and mental illness-related self-stigma, with participants in the service co-producer and service user group showing a faster rate of change compared to the control group. There were no statistically significant differences between the service co-producer and service user group, suggesting that Healing Space exerted a comparable influence on both groups of students. Additionally, the program did not yield statistically significant findings in indicators of social connectedness. Implications for research, practice, and policy are discussed.